The Pink City Jaipur: Study and Analysis of Historical Forts: Exploring the Charm and Glory of Jaipur's Historical Forts (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Royal palaces and forts with big courtyards and corridors, colorful cultural heritage and richembellishments around picturesque landscape was the motivation behind the research on palaces andforts of Jaipur. Jaipur is a dream city with its deep rooted culture and heritage. The only planned city ofits time was built by Maharaja Sawai Jai Singh II in 1727 A.D. and has many splendid monuments. Theforts of Jaipur district evolved from the time period of 11th to 17th century. The name to the city givenGulabi Nagari or pink city is due to the use of pink sandstone enriching it with an unresisting charmworldwide. The aim of this paper is to understand the ancient urban planning and design of fortresstowns and conservation and preservation of heritage buildings in context of increasing tourism. Theobjective of this paper is to critically analyze the ancient urban planning rules for designing fortresstowns to explore the charm and glory, splendor and bright colorful traditions of Jaipur which attractsboth in house people and tourists across India and abroad.